Medical image of the week: pulmonary artery sling - Agrawal A (Southwest Journal of Pulmonary and Critical Care, 2017)
No abstract available. Article truncated after 150 words. A 42-year-old year woman with asthma was admitted to the hospital with an asthma exacerbation. The patient complained of dyspnea on exertion, two-pillow orthopnea and bipedal edema. An echocardiogram showed a severely dilated right ventricle (RV) with elevated right ventricular systolic pressure of 71 mmHg. The systolic left ventricular (LV) function was also reduced with an ejection fraction of 45%. Computerized tomography (CT) of the chest showed an aberrant origin of the left pulmonary artery (PA) creating a pulmonary artery sling with mild tracheal narrowing (Figure 1, arrow). Cardiac magnetic resonance imaging (MRI) confirmed the presence of a pulmonary artery sling with the aberrant origin of the left PA from the right PA (Figure 2). Cardiac catheterization showed a mean PA pressure of 46mmHg with LV end diastolic pressure of 12mm Hg. The patient was diagnosed with WHO Group I pulmonary hypertension and started on treatment with sildenafil with a …